Use of sleep care guidelines in a surgical intensive care unit reduces noise levels and improves patient-reported sleep quality. Issue 4 (14th June 2011) - Koch, Susan; Noble, Helen
Abstract : Commentary on: Li SY Wang TJ Vivienne Wu SF . Efficacy of controlling night-time noise and activities to improve patients' sleep quality in a surgical intensive care unit. J Clin Nurs 2011 ;20 : 396 –407 .